The Effect of Chitosan and Sorbitol Addition in The Bioplastics Production from Mung Bean Starch (Nusantara Science and Technology Proceedings)
Plastics pollution is a worldwide concern causing many problems in our environment. Plastics were difficult to recycle. Therefore, biodegradable materials such as starch are appealing to replace fossil-based plastics. Starch-based plastics were blended with another natural polymer like chitosan and sorbitol as a plasticizing agent to improve their properties. In this study, the mechanical properties and degradability of the films were evaluated. The mechanical parameter studied were tensile strength, elongation, and young’s modulus. A higher ratio of chitosan in the blend would increase the tensile strength and young’s modulus. The film consisted of 40% chitosan in polymer blend and 20% sorbitol resulted in 13.33 MPa on tensile strength and 241.98 MPa on young's modulus. On the other hand, the more sorbitol added in polymer blends increased the film elongation and decreased other parameters studied. With 60% sorbitol added into the blends resulted in greater film elongation but low tensile strength. All films blended could degrade in a relatively short time, about 6 to 16 days, with the presence of EM4 microorganisms.